A comprehensive analysis of clinical, quality of life, and cost-effectiveness outcomes of key treatment options for benign prostatic hyperplasia - Chughtai, Bilal; Rojanasarot, Sirikan; Neeser, Kurt; Gultyaev, Dmitry; Fu, Shuai; Bhattacharyya, Samir K.; El-Arabi, Ahmad M.; Cutone, Ben J.; McVary, Kevin T. (PloS one, 2022)
Treatment options for men with moderate-to-severe lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) have variable efficacy, safety, and retreatment profiles, contributing to variations in patient quality of life and healthcare costs. This study examined the long-term cost-effectiveness of generic combination therapy (CT), prostatic urethral lift (PUL), water vapor thermal therapy (WVTT), photoselective vaporization of the prostate (PVP), and transurethral resection of the prostate (TURP) for the treatment of BPH. A systematic literature review was performed to identify clinical trials of CT, PUL, WVTT, PVP, and TURP that reported change in International Prostate Symptom Score (IPSS) for men with BPH and a prostate volume ≤80 cm 3 . A random-effects network meta‐analysis was used to account for the differences in patient baseline clinical characteristics between trials. An Excel-based Markov model was developed with a cohort of males with a mean age of 63 and an average IPSS of 22 to assess the cost-effectiveness of these treatment options at 1 and 5 years from a US Medicare perspective. Procedural and adverse event (AE)-related costs were based on 2021 Medicare reimbursement rates. Total Medicare costs at 5 years were highest for PUL ($9,580), followed by generic CT ($8,223), TURP ($6,328), PVP ($6,152), and WVTT ($2,655). The total cost of PUL was driven by procedural ($7,258) and retreatment ($1,168) costs. At 5 years, CT and PUL were associated with fewer quality-adjusted life years (QALYs) than WVTT, PVP, and TURP. Compared to WVTT, the incremental cost-effectiveness ratios (ICERs) for both TURP and PVP were above a willingness-to-pay threshold of $50,000/QALY (TURP: $64,409/QALY; PVP: $87,483/QALY). This study provides long-term cost-effectiveness evidence for several common treatment options for men with BPH. WVTT is an effective and economically viable treatment in resource-constrained environments.